Juan de Castellanos y su obra Elegías de Varones Ilustres de Indias a través de William Ospina - Cruz Moyano, Diego Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2012)
Este  ensayo  presenta  a  Juan  de Castellanos  como  el  personaje  que  introdujo literariamente a América en el Viejo Mundo. Caracteriza la obra Elegías de Varones Ilustres de Indias, el contexto de civilización y barbarie en el cual nació el texto, producto del encuentro cultural  y geográfico entre España y América, y  refiere aspectos sobresalientes de la vida del autor de las Elegías. Palabras clave:Elegías de Varones Ilustres de Indias, civilización y barbarie, crónica, ilustre.Abstract:This article presents to Juan de Castellanos as the character who introduced the literary aspect of America in the Old World. It characterizes the work Elegías de Varones Ilustres de Indias [Elegies of Illustrious Men of the Indies], the civilization and barbarism context in which the text was created, a result of the cultural and geographical union  between Spain  and America. The most  relevant aspects of writer life are also worked.Key words:elegies, civilization and barbarism, chronicle, illustrious.